A Comprehensive Review and Bifactor Modeling Analysis of the Brief COPE. (October 2022) - Rodrigues, Filipe; Figueiredo, Nuno; Rodrigues, José; Ferreira, Regina; Hernández-Mendo, Antonio; Monteiro, Diogo
The Brief COPE is a measure of coping strategies that contains 14 factors. The purpose of this research was twofold: (a) examine the psychometric proprieties of the Brief Cope in previous studies; and (b) perform Confirmatory Factor Analyses (CFA) with second-order model and bifactor model specifications that could be used to assess the best model that represents the 14 coping strategies inherent to the instrument. In order to meet the first objective, a bibliographic review of published peer-reviewed studies between 1997 and 2021 was conducted. Results from the review identified 50 studies, of which 21 used exploratory factor analysis, 28 CFA and one study test-retest analysis. Seventeen studies used the entire correlated 14-factor structure. However, only 11 studies conducted a CFA. For the second objective, a sample of 472 working class individuals (female = 278) with a mean work experience of 19.06 years (SD = 11, 92) were recruited. We tested several model specifications, convergent and discriminant validity analysis. We found the correlated 14-factor structure of the Brief COPE to have good psychometric properties. The second-order and bifactor model specifications displayed poor fit or did not converge, respectively. The measure showed good convergent and discriminant validity, and the subscales showed adequate internal consistency. We provide further validity and reliability of the correlated 14-factor structure, evidencing that this measure can assess coping mechanisms. Second-order model specifications need further testing and empirical evidence to support such hierarchical categorization.